ANALISIS STABILITAS MULTI MACHINE PADA ISLAND MODE SISTEM KELISTRIKAN BALI - Bayu Suarsa, I Gede; Gede Manuaba, Ida Bagus; Sari Hartati, Rukmi (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p14, 2020)
Modern electrical systems are characterized by extensive interconnection systems with the need for electrical energy and control depending on the control system. One electricity system that has been widely interconnected is the Bali electricity system. The Bali system using island mode has four generating units that can supply electrical energy needs including UP Pesanggaran, UP Celukan Bawang, UP Gilimanuk and UP Pemaron. But it must be remembered in supplying electrical energy needs are also affected by the constant change in load, resulting in instability in the electrical system. So the need for a control system that can increase the value of damper such as the Power System Stabilizer (PSS). PSS can be used to reduce frequency oscillations when interference occurs, but for PSS design it gives less good performance in different operating conditions. Problems with PSS occur due to errors in modeling, input value input, and topology variations. Efforts are made to reduce errors in PSS by using methods that are expected to overcome this problem, namely the fuzzy logic controller.The results of the analysis show that the system performance index using fuzzy logic is 78.6064. Fuzzy logic has the ability to damp better and reduce errors better.